A Fungal-Selective Cytochrome bc1 Inhibitor Impairs Virulence and Prevents the Evolution of Drug Resistance. Issue 8 (18th August 2016) - Vincent, Benjamin M.; Langlois, Jean-Baptiste; Srinivas, Raja; Lancaster, Alex K.; Scherz-Shouval, Ruth; Whitesell, Luke; Tidor, Bruce; Buchwald, Stephen L.; Lindquist, Susan
Summary: To cause disease, a microbial pathogen must adapt to the challenges of its host environment. The leading fungal pathogen Candida albicans colonizes nutrient-poor bodily niches, withstands attack from the immune system, and tolerates treatment with azole antifungals, often evolving resistance. To discover agents that block these adaptive strategies, we screened 300, 000 compounds for inhibition of azole tolerance in a drug-resistant Candida isolate. We identified a novel indazole derivative that converts azoles from fungistatic to fungicidal drugs by selective inhibition of mitochondrial cytochrome bc 1 . We synthesized 103 analogs to optimize potency (half maximal inhibitory concentration 0.4 μM) and fungal selectivity (28-fold over human). In addition to reducing azole resistance, targeting cytochrome  bc 1 prevents C. albicans from adapting to the nutrient-deprived macrophage phagosome and greatly curtails its virulence in mice. Inhibiting mitochondrial respiration and restricting metabolic flexibility with this synthetically tractable chemotype provides an attractive therapeutic strategy to limit both fungal virulence and drug resistance. Graphical Abstract: Highlights: 300, 000 compound screen identifies indazole that reverses fluconazole resistance Target identified as mitochondrial cytochrome bc 1 Optimized potency and fungal selectivity through chemical synthesis Impairing cytochrome bc 1 restricts carbon source utilization and virulence Abstract : Vincent et al. use a phenotypic screen to discover and optimize a series of indazoles that reverse resistance to triazole antifungals in the pathogenic fungus C. albicans . The indazoles target cytochrome bc 1, restricting carbon source utilization, macrophage escape, and virulence.